A Green Synthesis of Iron/Copper Nanoparticles as a Catalytic of Fenton-like Reactions for Removal of Orange G Dye (Baghdad Science Journal, 2022)
This research paper studies the use of an environmentally and not expensive method to degrade Orange G dye (OG) from the aqueous solution, where the extract of ficus leaves has been used to fabricate the green bimetallic iron/copper nanoparticles (G-Fe/Cu-NPs). The fabricated G‑Fe/Cu-NPs were characterized utilizing scanning electron microscopy, BET, atomic force microscopy, energy dispersive spectroscopy, Fourier-transform infrared spectroscopy and zeta potential. The rounded and shaped as like spherical nanoparticles were found for G-Fe/Cu‑NPs with the size ranged 32-59 nm and the surface area was 4.452 m2/g. Then the resultant nanoparticles were utilized as a Fenton-like oxidation catalyst. The degradation efficiency of OG dye highly depends on H2O2 concentration (1.7-5.28 mM), catalyst dose (0.4-1.6 g/L), pH (2-7), initial OG concentration (25-75 mg/L), and temperature (20-50 ℃). Batch experiments showed that 94.8 % of 50 mg/L of OG dye was removed within the optimum peroxide concentration, dose, pH and temperature which were 3.52 mM, 1 g/L, 3, and 40℃ respectively along with 30 min contact time. The results of kinetic models showed that OG removal followed the second-order model. Finally, the thermodynamic study of reaction was also examined and concluded to endothermic reaction with 29.725 kJ/mol activation energy.